2001
DOI: 10.1086/319340
|View full text |Cite
|
Sign up to set email alerts
|

Search for Primary Infection by Pneumocystis carinii in a Cohort of Normal, Healthy Infants

Abstract: To determine whether Pneumocystis carinii is associated with clinical illness in the competent host, 107 normal, healthy infants were enrolled in a 2-year prospective cohort study in Chile. P. carinii was identified by specific stains and nested--deoxyribonucleic acid (DNA) amplification of the large subunit mitochondrial ribosomal ribonucleic acid gene of P. carinii f. sp. hominis, and seroconversion was assessed by enzyme-linked immunosorbent assay of serum samples drawn every 2 months. P. carinii DNA was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
215
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(230 citation statements)
references
References 38 publications
11
215
0
4
Order By: Relevance
“…These results reinforce the idea that infants could constitute an important part of the P. jirovecii reservoir (Durand-Joly et al, 2003;Nevez et al, 2001;Totet et al, 2003a;Vargas et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results reinforce the idea that infants could constitute an important part of the P. jirovecii reservoir (Durand-Joly et al, 2003;Nevez et al, 2001;Totet et al, 2003a;Vargas et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…An association between Pneumocystis primary infection and sudden infant death syndrome (SIDS) has been reported in autopsy studies (Morgan et al, 2001;Vargas et al, 1999Vargas et al, , 2001. Pneumocystis has also been reported in noncomparative studies in infants from Oxford, UK or Rochester and Yale, USA (Morgan et al, 2001;Vargas et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, several populations have been identified as being colonized by the fungus. Low burden of P. jirovecii organisms have been detected using PCR assays in patients with various levels of immunodeficiency (Nevez et al, 1999a;Nevez et al, 1999b), with acute or chronic pulmonary diseases (Calderon et al, 1996;Armbruster et al, 1997;Sing et al, 1999b;Nevez et al, 2002), immunonaive infants with P. jirovecii primary infection (Nevez et al, 2001a, Vargas et al, 2001, pregnant women with physiological immunity changes (Vargas et al, 2003), and health care workers in contact with patients with PCP (Miller et al, 2001, Durand-Joly et al, 2003, reviewed in Peterson et al, 2005. In fact, Pneumocystis infections can have a large spectrum of presentations, of which PCP in immunocompromised patients may represent only a part, while mild infections such as colonization may constitute the major part.…”
Section: Colonized Subjects As Potential Sources Of P Jiroveciimentioning
confidence: 99%
“…Although exposure to P. carinii is nearly universal, as demonstrated by the appearance of anti-P. carinii antibody in 85% of children by the age of 20 mo (35), a period of immunosuppression is essential for the development of clinical disease (15,34). Several studies have demonstrated a positive correlation between the degree of inflammation and the severity of disease (4,23,36), suggesting that the pathogenesis of Pneumocystis pneumonia (PcP) is primarily inflammatory in nature, in that infection with P. carinii is necessary to cause pneumonia, but certain aspects of the immune response against P. carinii are responsible for the associated pathophysiology (30,39).…”
mentioning
confidence: 99%